Merchants, ports and hinterlands : the building of sea-port structures in the Early Modern Porto - Barros, Amândio Jorge Morais (2008)
Emerging in the Middle Ages, Porto became one of the most important ports of the Iberian Peninsula. The city’s affirmation over the nearby territory was accompanied by the expansion of business towards the northern markets of Flanders, Brabant, Great Britain and northern France (Brittany and Normandy), stimulating the emergence of a merchant navy, and inspiring a set of engineering works meant to organize the harbour. With this paper, I’ll pay attention to the role performed by small ports and apparently modest business centres in the building and organization of the first global age. The history of such port like Porto will contribute to enlighten fields of interaction that existed between the port-cities and their umlands and hinterlands, which supported its economy,mould a significant part of its society, and influenced its cultural standards. In this study I’ll present the most important facts of the process of territorial domination, and the way things were conducted in order to get effective its mercantile economy. Charts will be presented and comment, once they are very informative to this evolution, and I’ll also emphasize the international context in which it occurred.